Occurrence of Campylobacter and Salmonella spp. in ducks and duck eggs - Sarif, Nor Faiza; Abdul Aziz, Saleha (2012)
Seventy-five cloacae swab samples from ducks were collected for Campylobacter spp. and Salmonella spp. isolation and 32 duck eggs were purchased for Salmonella isolation. The samples were collected and purchased from two backyard and a government farms. The shells and contents of the eggs were examined for Salmonella spp. All cloacae samples were cultured for Campylobacter spp. by direct plating on Campylobacter selective agar, mCCDA agar and for Salmonella isolation, preenrichment and enrichment were done before plating on XLT4 agar. The isolates of Salmonella and Campylobacter were identified by colony morphology, gram staining, cell morphology and biochemical tests. Nine samples from 3 farms (12%) were positive for Campylobacter spp. A total of 12 samples (8.9%) were positive for Salmonella spp. The eggs were negative for Salmonella spp. This study revealed that ducks are carriers for Campylobacter spp. and Salmonella spp. Thus proper hygiene management of the animals and farms may help to control infection. This is to avoid contamination of carcasses during processing. These bacteria are zoonotic and may cause gastroenteritis in humans.